Temporal evolution of sulfated zirconia sol-gel during dip coating: Analysis of mass drainage with time-varying refractive index - Michels, A. F.; Menegotto, T.; Santilli, Celso Valentim [UNESP]; Horowitz, F. (Elsevier, 2006)
The formation of sulfated zirconia films from a sol-gel derived aqueous suspension is subjected to double-optical monitoring during batch dip coating. Interpretation of interferometric patterns, previously obscured by a variable refractive index, is now made possible by addition of its direct measurement by a polarimetric technique in real time. Significant sensitivity of the resulting physical thickness and refractive index curves (uncertainties of ±7 nm and ±0.005, respectively) to temporal film evolution is shown under different withdrawal speeds. As a first contribution to quantitative understanding of temporal film formation with varying nanostructure during dip coating, detailed analysis is directed to the stage of the process dominated by mass drainage, whose simple modeling with temporal t-1/2 dependence is verified experimentally. © 2006 Elsevier B.V. All rights reserved.
Keywords: Films and coatings; Measurement techniques; Optical properties; Rheology; Sol-gel, aerogel and solution chemistry; Coatings; Measurement theory; Polarimeters; Refractive index; Sol-gels; Solutions; Suspensions (components); Aqueous suspension; Dip coating; Interferometric patterns; Mass drainage; Solution chemistry; Zirconia